(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Background: Menstrual blood banking is an emerging area of regenerative medicine that utilizes menstrual blood-derived stem cells for potential therapeutic applications in tissue repair and the treatment of various degenerative diseases. Despite increasing scientific advances, awareness regarding menstrual blood banking among young women remains limited, highlighting the need to assess their level of knowledge. Objectives: To assess the knowledge regarding menstrual blood banking among female undergraduate students and determine its association with selected demographic variables. Methods: A quantitative, descriptive cross-sectional study was conducted among 100 female undergraduate students at Purnodaya Mahila Mahavidyalaya College, Varanasi, Uttar Pradesh. Participants were selected using a non-probability convenience sampling technique. Data were collected using a structured questionnaire consisting of demographic variables and a 15-item knowledge questionnaire on menstrual blood banking. Descriptive and inferential statistics were used for data analysis. Results: The study revealed that 69% of participants had moderate knowledge, 18% had adequate knowledge, and 13% had inadequate knowledge regarding menstrual blood banking. No statistically significant association was observed between knowledge scores and selected demographic variables (p > 0.05). Conclusion: The findings indicate that most female undergraduate students possess only moderate knowledge regarding menstrual blood banking. Structured educational programmes and awareness initiatives are recommended to improve knowledge and promote informed decision-making regarding menstrual blood stem cell banking.